Fun game–based learning improves gross motor skills in early primary school children - Ahmad Muttaqin Darussalam; Sugiharto Sugiharto; Sapto Adi (Physical Education and Sports: Studies and Research, 2025)
Background: Children who face difficulties in gross motor skill development may withdraw from physical activities, experience low self-esteem, and suffer from social anxiety. Physical education plays a vital role in fostering gross motor development, especially when delivered through enjoyable and engaging activities such as fun games. Objectives: This study aimed to investigate the impact of fun game–based learning on the development of gross motor skills in early primary school children. Methods: The study employed a quasi-experimental design with a non-equivalent control group. A total of 36 second-grade students from SDIT Mutiara Hati in Malang participated in this study. Participants were assigned to one of three groups: a control group, a group-based fun games intervention, and an individual-based fun games intervention. The interventions were implemented three times a week for 30 minutes over a period of seven weeks. Gross motor skills were measured before and after the intervention using the Test of Gross Motor Development–Third Edition (TGMD-3), a reliable and validated instrument. Data were analyzed using homogeneity and normality tests, paired-sample t-tests, one-way ANOVA, and Tukey's HSD post hoc tests, with a significance level set at p < 0.05 (SPSS version 25). Results: Both the individual and group fun game–based learning interventions produced significant improvements in gross motor skills compared with the control group (p < 0.05). Moreover, a significant difference was found between the two intervention types, indicating that the mode of fun game delivery influences outcomes (p < 0.05). Conclusions: Fun game–based learning, whether delivered individually or in groups, effectively enhances gross motor skills among early primary school children. Additionally, individual fun game–based learning demonstrated a significantly greater improvement compared to group-based learning.